2019
DOI: 10.1136/bjophthalmol-2019-314752
|View full text |Cite
|
Sign up to set email alerts
|

Practice patterns to decrease myopia progression differ among paediatric ophthalmologists around the world

Abstract: IntroductionMyopia is a worldwide epidemic. Plethora of treatments are offered to decrease myopia progression. In this study, we compared between different geographical areas worldwide the practice patterns used by paediatric ophthalmologists to decrease the progression of myopia.MethodsGlobal responses to a questionnaire were analysed (n=794) for demographic variations. Pharmacological, optical and behavioural categories were defined as effective or ineffective based on the current scientific peer reviewed li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…A combination of all three modalities was the most popular in most regions, apart from Central-Asia where the prevalence of optical and behavioural combinations was higher. 324 Currently, numerous publications provide the evidence that combined treatment with atropine and ortho-K lenses provides an additive benefit in myopia control. [325][326][327][328] In a preliminary study, during a 1-year follow-up, the combination of ortho-K and atropine 0.01% ophthalmic solution was more effective in slowing axial elongation than ortho-K monotherapy in 8-12 years old children.…”
Section: Combination Of Interventionsmentioning
confidence: 99%
“…A combination of all three modalities was the most popular in most regions, apart from Central-Asia where the prevalence of optical and behavioural combinations was higher. 324 Currently, numerous publications provide the evidence that combined treatment with atropine and ortho-K lenses provides an additive benefit in myopia control. [325][326][327][328] In a preliminary study, during a 1-year follow-up, the combination of ortho-K and atropine 0.01% ophthalmic solution was more effective in slowing axial elongation than ortho-K monotherapy in 8-12 years old children.…”
Section: Combination Of Interventionsmentioning
confidence: 99%
“…Thus, the vast majority of young myopes progress. The previously described survey of paediatric ophthalmologists 73 indicates that fast progression is the primary reason to intervene, but it is becoming evident that past progression does not predict future progression. Hernandez et al .…”
Section: When Should Myopia Control Be Implemented and On Which Childmentioning
confidence: 99%
“…To date, no evidence-based clinical management guideline for myopic children has been established to tailor treatment based on expected future myopia progression. Past progression has been the most favored indicator among pediatric ophthalmologists for initiating myopia progression therapy, and the average threshold used is -1 D. 22 However, using past progression has obvious pitfalls. Children with slow progression (>-0.50 D/y) in the first year of our study had a mean (± SD) progression of -0.41 ± 0.33 D/y, indicating that about 16% of children (one in six) that progress by less than 0.50 in year 1 will progress by -0.74 D in the subsequent 2 years.…”
Section: Myopia Progression In the First Year And Subsequent 2-year Mmentioning
confidence: 99%
“…A survey of pediatric ophthalmologists reported that the most common indication for initiating myopia control treatment was prior rate of progression. 22 By association, this criterion has been used to predict faster future progression, but there is limited information available to link myopia progression during a given year with subsequent myopia progression in a longitudinal cohort study.…”
Section: Introductionmentioning
confidence: 99%